A layered ordered@disordered core-shell structure lithium ion battery positive electrode material and its preparation method and application

Preparation of layered ordered @ disordered core-shell structure lithium-ion battery positive electrode material through high-temperature molten salt method, solving the problem of unstable structure and surface chemical properties of high-nickel layered ternary materials, significantly improving electrochemical performance and cycle life , achieving high specific capacity and good battery performance.

CN115084466BActive Publication Date: 2025-01-07XI AN JIAOTONG UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210744453.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-06-28
Publication Date
2025-01-07
Estimated Expiration
2042-06-28

AI Technical Summary

Technical Problem

The cycle life of the positive electrode material of high-nickel layered ternary lithium-ion battery is poor, mainly due to its unstable structural structure and unstable surface chemical properties, which affects its electrochemical properties.

Method used

The positive electrode material of the layered ordered @ disordered core-shell structure lithium-ion battery is prepared by high-temperature molten salt method, and the precursor is prepared by co-precipitation method, and then mixed with lithium salt and calcination at high temperature, combined with high-temperature molten salt treatment, to regulate the roasting temperature and molten salt The ratio was to extract lithium/oxygen from the surface of the layered structure to prepare Li(NixCoyMn1-x-y)O2@Li1-m(NixCoyMn1-x-y)1+mO2 core-shell structure material with different shell thicknesses.

Benefits of technology

The electrochemical performance of the material is improved. The first discharge capacity is 2.0~4.3V and 0.1C current density reaches 183~228mAh g-1. The capacity retention rate reaches 91% after 50 cycles. The material particles are uniformly distributed and the particle size is controllable. Suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115084466B_ABST
    Figure CN115084466B_ABST
Patent Text Reader

Abstract

The present invention discloses a layered ordered@disordered core-shell structure lithium ion battery positive electrode material and its preparation method and application, belonging to the technical field of lithium ion battery positive electrode materials. The present invention adopts a high-temperature molten salt method, and its preparation process is as follows: firstly, a hydroxide precursor or a carbonate precursor is prepared by a coprecipitation method, and then a layered ordered oxide Li (Ni x Co y Mn 1‑x‑y )O2, and then evenly mix it with an appropriate amount of molten salt and calcine it at high temperature to extract the layered ordered structure Li(Ni x Co y Mn 1‑x‑y )O2 surface lithium / oxygen to obtain Li(Ni x Co y Mn 1‑x‑y )O2@Li 1‑m (Ni x Co y Mn 1‑x‑y ) 1+m O2 core-shell structure material. This method can prepare core-shell structure oxide materials with different shell thicknesses by adjusting the molten salt ratio and calcination temperature in the high-temperature molten salt section, and has excellent cycle stability, which can be effectively used in the preparation of lithium-ion batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium ion positive electrode material preparation, and specifically relates to a layered ordered@disordered core-shell structure lithium ion battery positive electrode material and a preparation method and application thereof. Background Art

[0002] As an important device for storing and converting electrical energy, batteries have been the main way for people to use electrical energy for many years. Today, the batteries on the market mainly include nickel-cadmium batteries, lead-acid batteries and lithium-ion batteries. Among them, lithium-ion batteries are widely used in many fields such as portable electronic devices, military equipment, smart grids, aerospace, electric vehicles, etc. due to their advantages such as high energy density, no memory effect, small self-discharge effect and long cycle life. However, with the application of mobile energy storage, power batteries and the innovation of related technical fields, people have put forward higher requirements on the energy density, rate performance, endurance, use cost and safety of lithium-ion batteries. Lithium-ion batteries mainly include four parts: positive electrode, negative electrode, diaphragm and electrolyte. Among them, the specific capacity of the positive electrode material is lower than that of the negative electrode material, which limits the overall performance of the lithium-ion battery. Therefore, improving the performance of the positive electrode material of lithium-ion batteries has great value and practical significance.

[0003] High nickel layered ternary cathode material Li(Ni x Co y Mn 1-x-y )O2(x≥0.6, referred to as NCM, space group ) has good application prospects due to its low price, high capacity, and high energy density. Increasing the nickel content can increase the specific capacity of the material. For example, when the nickel content is 0.8, the layered ternary material LiNi 0.8 Co 0.1 Mn 0.1 The discharge capacity of O2 (NCM811) is about 200 mAh g -1 , much higher than other traditional cathode materials, such as LiCoO2 (about 150mAh g -1 )、LiFePO4(about 160mAh g -1 ) etc. Therefore, high nickel ternary materials are the inevitable trend of the future development of lithium-ion battery materials and technologies.

[0004] Although high-nickel layered ternary materials exhibit high discharge specific capacity, their cycle life is poor, limiting their commercial application. This is mainly due to the unstable structure and surface chemical properties of high-nickel materials. During the electrochemical cycle, the high-nickel layered structure is prone to irreversible structural changes, reducing its electrochemical activity. On the other hand, the residual lithium on the surface of the high-nickel material reacts with CO2 and H2O in the air to easily generate impurities such as Li2CO3 and LiOH, increasing the interfacial impedance of the positive electrode material. Therefore, improving the structural and surface chemical stability is the key to improving the electrochemical cycle performance of high-nickel layered ternary materials. At present, the preparation of high-nickel layered ternary materials is generally divided into two stages: the preparation of precursors by coprecipitation method and the preparation of lithium-embedded oxides by high-temperature solid phase method. The high-temperature solid phase reaction needs to be carried out in an oxygen atmosphere to oxidize the divalent nickel in the precursor to trivalent nickel. The surface chemical properties of the material obtained by this method are unstable, and impurities such as lithium hydroxide and lithium carbonate are easily generated, which seriously affect its electrochemical performance. Summary of the invention

[0005] In order to overcome the shortcomings of the above-mentioned prior art, the purpose of the present invention is to provide a layered ordered@disordered core-shell structure lithium ion battery positive electrode material and its preparation method and application. On the basis of lithium oxide insertion, the lithium / oxygen on the surface of the layered structure is extracted by a high temperature molten salt method, and the calcination temperature and the molten salt ratio are adjusted to effectively prepare Li(Ni x Co y Mn 1-x-y )O2@Li 1-m (Ni x Co y Mn 1-x-y ) 1+m O2 core-shell structure material with excellent electrochemical properties.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions:

[0007] The invention discloses a method for preparing a layered ordered@disordered core-shell structure lithium ion battery positive electrode material, comprising: preparing a hydroxide precursor or a carbonate precursor by a coprecipitation method, and then preparing a layered ordered oxide Li(Ni) by high temperature calcination. x Co y Mn 1-x-y )O2, and then the layered ordered oxide Li(Ni x Co y Mn 1-x-y )O2 is uniformly mixed with an appropriate amount of molten salt and calcined at high temperature to extract the layered ordered structure Li(Ni x Co y Mn 1-x-y)O2 surface lithium / oxygen to obtain layered ordered@disordered core-shell structure lithium ion battery positive electrode material Li(Ni x Co y Mn 1-x-y )O2@Li 1-m (Ni x Co y Mn 1-x-y ) 1+m O2, where 0.05≤m≤0.15, 0.60≤xm≤1.00; 0.00≤ym≤0.40.

[0008] Preferably, the method for preparing the layered ordered@disordered core-shell structure lithium ion battery positive electrode material comprises the following steps:

[0009] 1) Prepare solution

[0010] According to the chemical formula Li(Ni x Co y Mn 1-x-y )O2 ratio, 0.60≤xm≤1.00; 0.00≤ym≤0.40, weigh one or more nickel salts, cobalt salts and manganese salts, add water to fully dissolve to prepare a concentration of 0.5-3 mol·L -1 of saline solution;

[0011] 2) Co-precipitation treatment

[0012] Water, precipitant solution, ammonia buffer and the solution prepared in step 1) with a concentration of 0.5 to 3 mol·L -1 and a salt solution to obtain a mixed solution, wherein the pH value of the mixed solution is 8.0 to 12.0; stirring and reacting at 40 to 70° C. for 1 to 100 hours, filtering, washing and drying the powder obtained by the reaction to obtain a precursor material;

[0013] 3) High temperature calcination treatment

[0014] The precursor material and lithium salt are mixed evenly, heated from room temperature to 600-800°C in air or oxygen atmosphere, and calcined for 4-20h to obtain the layered oxide material Li(Ni x Co y Mn 1-x-y )O2;

[0015] 4) High temperature molten salt treatment

[0016] The layered oxide material Li(Ni x Co y Mn 1-x-y)O2 and molten salt are mixed evenly, heated from room temperature to 500-900°C in air or oxygen atmosphere, and calcined for 2-15h. The calcined powder material is washed and dried to obtain a layered ordered@disordered core-shell structure lithium ion battery positive electrode material Li(Ni x Co y Mn 1-x-y )O2@Li 1-m (Ni x Co y Mn 1-x-y ) 1+m O2, 0.05≤m≤0.15.

[0017] Preferably, in step 1), the nickel salt is Ni(CH3COO)2·4H2O, NiSO4·6H2O, NiCl2·6H2O or Ni(NO3)2·6H2O; the cobalt salt is Co(CH3COO)2·4H2O, CoCl2·6H2O, CoSO4·7H2O or Co(NO3)2·6H2O; the manganese salt is Mn(CH3COO)2·4H2O, MnSO4·H2O, MnCl2·4H2O or Mn(NO3)2·4H2O.

[0018] Preferably, in step 2), the concentration of the precipitant solution is 2 to 6 mol·L -1 It is prepared by dissolving sodium hydroxide or sodium carbonate in water; the concentration of ammonia buffer is 1 to 10 mol·L -1 .

[0019] Preferably, in step 2), the coprecipitation treatment is carried out in a reactor, 1 L of deionized water is added to the reactor, and the concentration of 0.5 to 3 mol·L -1 The salt solution, precipitant solution and ammonia buffer solution are added into the reactor; wherein the inlet speed of the salt solution is controlled to be 0.5-20 mL / min, and the inlet speed of the ammonia buffer solution is controlled to be 0.2-10 mL / min.

[0020] Preferably, in step 2), the stirring reaction speed is controlled to be 200-500 r / min.

[0021] Preferably, in step 3), the molar ratio of the precursor material to the lithium salt is 1:1.01 to 1:1.10; the lithium salt is LiOH·H2O, LiCH3COO, LiNO3 or Li2CO3.

[0022] Preferably, in step 4), the layered oxide material Li(Ni x Co y Mn 1-x-y)The mass ratio of O2 to molten salt is 1:1 to 1:5; the molten salt is one or more of Li2MoO4, NaCl, KCl, LiCl and LiNO3.

[0023] The present invention also discloses a layered ordered@disordered core-shell structure lithium ion battery positive electrode material prepared by the above preparation method, and the first discharge capacity ranges from 183 to 228 mAh g at 2.0 to 4.3 V and 0.1 C current density. -1 After 50 cycles, the capacity retention rate is over 90%.

[0024] The present invention also discloses the use of the above-mentioned layered ordered@disordered core-shell structure lithium ion battery positive electrode material in the preparation of lithium ion batteries.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] The preparation method disclosed in the present invention adopts a high-temperature molten salt method, firstly, a precursor material is prepared by coprecipitation, and then mixed with lithium and calcined to obtain a high-nickel positive electrode material with a layered ordered structure, and then mixed with an appropriate amount of molten salt, calcined at high temperature, and Li / O on the surface of the crystal is extracted to obtain a layered ordered@disordered core-shell structure oxide material. The preparation method can prepare core-shell structure materials with different shell thicknesses by adjusting the temperature of the high-temperature molten salt section and the proportion of molten salt. And the material particles prepared by this method are evenly distributed, the particle size is controllable, and the batch uniformity is high. The process flow of the method described in the present invention is simple and controllable, easy to operate, and the surface chemistry and crystal structure of the material are stable, which is conducive to industrial production.

[0027] The layered ordered@disordered core-shell structure cathode material prepared by the present invention has excellent electrochemical performance, and the first discharge capacity reaches 183-228 mAh g at 2.0-4.3 V and 0.1 C current density. -1 After 50 cycles, the capacity retention rate reaches 91%. Therefore, it can be effectively used in the preparation of lithium-ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 This is a scanning electron microscope (SEM) image of the core-shell structure positive electrode material prepared in Example 1 of the present invention.

[0029] Figure 2 This is a high-resolution transmission electron microscopy (HRTEM) image of the core-shell structure positive electrode material prepared in Example 1 of the present invention.

[0030] Figure 3 This is the X-ray diffraction (XRD) spectrum of the core-shell structure positive electrode material prepared in Example 2 of the present invention.

[0031] Figure 4This is a cycle performance diagram of the core-shell structure positive electrode material prepared in Example 2 of the present invention.

[0032] Figure 5 This is a SEM image of the core-shell structure positive electrode material prepared in Example 3 of the present invention.

[0033] Figure 6 This is the first charge and discharge curve of the core-shell structure positive electrode material prepared in Example 4 of the present invention.

[0034] Figure 7 This is the XRD spectrum of the core-shell structure positive electrode material prepared in Example 5 of the present invention.

[0035] Figure 8 This is the first charge and discharge curve of the core-shell structure positive electrode material prepared in Example 5 of the present invention. DETAILED DESCRIPTION

[0036] In order to enable those skilled in the art to better understand the scheme of the present invention, the technical scheme in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

[0037] It should be noted that the terms "first", "second", etc. in the specification and claims of the present invention and the above-mentioned drawings are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the data used in this way can be interchanged where appropriate, so that the embodiments of the present invention described herein can be implemented in an order other than those illustrated or described herein. In addition, the terms "including" and "having" and any variations thereof are intended to cover non-exclusive inclusions, for example, a process, method, system, product or device that includes a series of steps or units is not necessarily limited to those steps or units that are clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or devices.

[0038] The present invention is further described in detail below in conjunction with the accompanying drawings:

[0039] Example 1

[0040] In this embodiment, according to the chemical formula LiNi 0.9 Mn 0.1 O2 ingredients.

[0041] A method for preparing LiNi with different shell thickness 0.9 Mn 0.1 O2@Li 0.95(Ni 0.9 Mn 0.1 ) 1.05 The method for O2 core-shell structure positive electrode material comprises the following steps:

[0042] Step 1. Solution preparation:

[0043] According to the molar ratio of nickel to manganese of 0.9:0.1, NiSO4·6H2O and MnSO4·H2O were weighed respectively, and deionized water was added and stirred to fully dissolve to prepare 3 mol L -1 (transition metal) salt solution; weigh sodium hydroxide solid and add deionized water to fully dissolve it to make a concentration of 6 mol L -1 Precipitant solution, i.e. sodium hydroxide solution; take an appropriate amount of concentrated ammonia water and add deionized water to dilute to 10 mol L -1 , to make an ammonia buffer solution.

[0044] Step 2. Co-precipitation:

[0045] Before the reaction started, 1L of deionized water was first added to the 5L reactor, and then nitrogen was introduced to expel the oxygen in the reactor. A peristaltic pump was used to inject the transition metal salt solution and ammonia buffer into the reactor from the feed port at feed rates of 0.5ml / min and 0.2ml / min, respectively, and the feed rate of the sodium hydroxide solution was adjusted to control the pH value of the solution in the reactor to 11.3. The reaction temperature was controlled to 70°C and the agitator speed was 500r / min. After 100h of reaction, the obtained product was filtered, washed, and dried to obtain a hydroxide precursor material.

[0046] Step 3. Calcination:

[0047] The hydroxide precursor particles obtained in step 2 are mixed with Li2CO3, and the ratio of the total molar amount of the transition metal salt to lithium is 1:1.1. The mixture is mixed in a ball mill and then placed in a muffle furnace in an oxygen atmosphere and calcined at 700°C for 20 hours to obtain a layered LiNi 0.9 Mn 0.1 O2.

[0048] Step 4. High temperature molten salt

[0049] The layered oxide material LiNi obtained in step 3 0.9 Mn 0.1 O2 and Li2MoO4 were evenly mixed in a mass ratio of 1:2, then placed in a muffle furnace filled with oxygen atmosphere and calcined at 500°C for 15h. The obtained powder was then fully washed with distilled water and dried to obtain a layered ordered@disordered core-shell composite high-nickel positive electrode material.

[0050] The layered ordered@disordered core-shell structure material prepared in this embodiment is spherical. Figure 1 As shown, the secondary particle size is about 10 μm, and the XRD spectrum shows that the prepared sample has a typical layered structure with a space group of Transmission electron microscopy of the samples Figure 2 As shown, it can be seen that the interior of the particle is an ordered layered structure, and the shell surface is a disordered layered structure with a thickness of about 2nm.

[0051] The charging and discharging performance test process of the positive electrode material prepared in this example is as follows:

[0052] Weigh an appropriate amount of the core-shell structure cathode material, acetylene black, and binder polyvinylidene fluoride (PVDF) prepared above in a mass ratio of 8:1:1, add them to N-methylpyrrolidone (NMP) to make a slurry, evenly coat the slurry on aluminum foil, and bake it in a vacuum drying oven at 80°C for 12 hours. After that, use a mold to cut it into pole pieces (diameter 12mm). With metal lithium sheet as the negative electrode, polypropylene film (Celgard 2400) as the separator, and LP30 as the electrolyte, CR2032 button batteries were assembled in a glove box filled with argon.

[0053] The electrochemical performance of the battery was tested at a voltage range of 2.0 to 4.3 V and different current densities. The results showed that the core-shell structure positive electrode material LiNi prepared in this embodiment 0.9 Mn 0.1 O2@Li 0.95 (Ni 0.9 Mn 0.1 ) 1.05 O2O2 at a current density of 0.1C (1C = 200mA g -1 The first charge and discharge capacities at the rate of 215 mAh g -1 .

[0054] Example 2

[0055] In this embodiment, according to the chemical formula LiNi 0.8 Co 0.1 Mn 0.1 O2 ingredients.

[0056] A method for preparing LiNi with different shell thicknesses 0.8 Co 0.1 Mn 0.1 O2@Li 0.9 (Ni 0.8 Co 0.1 Mn 0.1 ) 1.1 The method for O2 core-shell structure positive electrode material comprises the following steps:

[0057] Step 1. Solution preparation:

[0058] According to the molar ratio of nickel, cobalt and manganese elements of 0.8:0.1:0.1, the corresponding Ni(CH3COO)2·4H2O, Co(CH3COO)2·4H2O and Mn(CH3COO)2·4H2O salts were weighed respectively and prepared into 0.5 mol L -1 Mixed transition metal salt solution; weigh Na2CO3 and prepare a concentration of 2 mol L -1 precipitant solution; dilute the concentrated ammonia solution to 1 mol L -1 .

[0059] Step 2. Co-precipitation:

[0060] 1L of deionized water was added to a 5L reactor as the base liquid, and the transition metal salt solution and ammonia solution were injected into the reactor from the feed port at a feed rate of 20ml / min and 10ml / min respectively by a peristaltic pump, and the feed rate of the Na2CO3 solution was adjusted to control the pH value of the solution in the reactor to 8. The reaction temperature was controlled to 50°C and the stirrer speed was 500r / min. After reacting for 1h, the product obtained in the reactor was filtered, washed and dried to obtain a carbonate precursor material.

[0061] Step 3. Calcination:

[0062] The carbonate precursor particles obtained in step 2 were mixed with LiOH·H2O, and the ratio of the total molar amount of the transition metal salt to lithium was 1:1.01. The mixture was mixed evenly and placed in a muffle furnace filled with oxygen atmosphere and calcined at 800°C for 4 hours to obtain layered LiNi 0.8 Co 0.1 Mn 0.1 O2.

[0063] Step 4. High temperature molten salt

[0064] The layered oxide material LiNi obtained in step 3 0.8 Co 0.1 Mn 0.1 O2 and KCl were mixed evenly in a mass ratio of 1:1, and then placed in a muffle furnace for calcination at 700°C in an oxygen atmosphere for 8 hours. The obtained powder material was fully washed with distilled water and dried to obtain a layered ordered@disordered core-shell composite high-nickel positive electrode material LiNi 0.8 Co 0.1 Mn 0.1 O2@Li 0.9 (Ni 0.8 Co 0.1 Mn 0.1 ) 1.1 O2.

[0065] The secondary particle size of the layered ordered@disordered core-shell structure material prepared in this embodiment is about 2 μm, the thickness of the disordered shell layer is about 8 nm, and the XRD spectrum of the sample is as follows: Figure 3 As shown, it can be seen that the core-shell material has a tripartite layered structure

[0066] Battery assembly and charge-discharge performance test: The battery assembly and battery charge-discharge test methods are the same as those in Example 1. The results show that the LiNi prepared in this example 0.8 Co 0.1 Mn 0.1 O2@Li 0.9 (Ni 0.8 Co 0.1 Mn 0.1 ) 1.1 The first discharge capacity of the O2 cathode material at 0.1C is 213 mAh g -1 After 30 cycles, the capacity is still 205mAh g -1 .

[0067] Example 3

[0068] In this embodiment, according to the chemical formula LiNi 0.6 Co 0.2 Mn 0.2 O2 ingredients.

[0069] A method for preparing LiNi with different shell thicknesses 0.6 Co 0.2 Mn 0.2 O2@Li 0.85 (Ni 0.6 Co 0.2 Mn 0.2 ) 1.15 The method for O2 core-shell structure positive electrode material comprises the following steps:

[0070] Step 1. Solution preparation:

[0071] According to the molar ratio of nickel, cobalt and manganese elements of 0.6:0.2:0.2, the corresponding Ni(NO3)2·6H2O, Co(NO3)2·6H2O and Mn(NO3)2·4H2O salts were weighed respectively and deionized water was added to prepare 2 mol L -1 Weigh the sodium hydroxide solid and mix it with deionized water to a concentration of 4 mol L -1 precipitant solution; dilute the concentrated ammonia solution to 5 mol L -1 .

[0072] Step 2. Co-precipitation:

[0073] Add 1L of deionized water to a 5L reactor, and then continuously introduce nitrogen into the reactor to expel oxygen in the reactor. Use a peristaltic pump to inject the transition metal salt solution and ammonia solution into the reactor from the feed port at feed rates of 1.5ml / min and 2.0ml / min, respectively, and adjust the feed rate of sodium hydroxide solution to control the pH value of the solution in the reactor to 12. Control the reaction temperature to 60°C and the stirrer speed to 200r / min. After 50h of reaction, the product obtained in the reactor is filtered, washed, and dried to obtain a hydroxide precursor material.

[0074] Step 3. Calcination:

[0075] The hydroxide precursor particles obtained in step 2 were mixed with LiCH3COO, and the ratio of the total molar amount of the transition metal salt to lithium was 1:07. The mixture was mixed evenly and placed in a muffle furnace and calcined in air at 800°C for 16 hours to obtain layered LiNi 0.6 Co 0.2 Mn 0.2 O2.

[0076] Step 4. High temperature molten salt

[0077] The layered oxide material LiNi obtained in step 3 0.6 Co 0.2 Mn 0.2 O2 and NaCl were mixed evenly in a mass ratio of 1:5, and then placed in a muffle furnace for calcination at 900°C in air for 2h. The obtained powder material was fully washed with distilled water and dried to obtain a layered ordered@disordered core-shell composite high-nickel positive electrode material LiNi 0.6 Co 0.2 Mn 0.2 O2@Li 0.85 (Ni 0.6 Co 0.2 Mn 0.2 ) 1.15 O2.

[0078] The morphology of the core-shell structure cathode material prepared in this example is shown in Figure 5 It can be seen from the figure that the particles are spherical agglomerates, and the thickness of the disordered shell layer of the core-shell structure material is 10nm.

[0079] Battery assembly and charge-discharge performance test: The battery assembly and battery charge-discharge test methods are the same as those in Example 1. The results show that the LiNi prepared in this example 0.6 Co 0.2 Mn 0.2 O2@Li 0.85 (Ni 0.6 Co 0.2 Mn 0.2 ) 1.15The first discharge capacity of the O2 cathode material at 0.1C is 183 mAh g -1 , the capacity retention rate is 91% after 50 cycles.

[0080] Example 4

[0081] In this embodiment, according to the chemical formula LiNi 0.9 Co 0.05 Mn 0.05 O2 ingredients.

[0082] A method for preparing LiNi with different shell thicknesses 0.9 Co 0.05 Mn 0.05 O2@Li 0.92 (Ni 0.9 Co 0.05 Mn 0.05 ) 1.08 The method for O2 core-shell structure positive electrode material comprises the following steps:

[0083] Step 1. Solution preparation:

[0084] According to the molar ratio of nickel, cobalt and manganese elements of 0.9:0.05:0.05, the corresponding NiCl2·6H2O, MnCl2·4H2O and CoCl2·6H2O salts were weighed respectively, and deionized water was added to prepare 1 mol L -1 Weigh the sodium carbonate solid and add deionized water to fully dissolve it to make a concentration of 6 mol L -1 precipitant solution; dilute the concentrated ammonia solution to 8 mol L -1 .

[0085] Step 2. Co-precipitation:

[0086] First, 1L of deionized water was added to a 5L reactor, and a peristaltic pump was used to inject the transition metal salt solution and ammonia solution into the reactor from the feed port at feed rates of 5.0ml / min and 3.0ml / min, respectively. At the same time, the feed rate of the sodium carbonate solution was adjusted to control the pH value of the solution in the reactor to 8.5. The reaction temperature was controlled to 40°C and the stirrer speed was 450r / min. After reacting for 30h, the product obtained in the reactor was filtered, washed, and dried to obtain a carbonate precursor material.

[0087] Step 3. Calcination:

[0088] The carbonate precursor particles obtained in step 2 are mixed with LiNO3, and the ratio of the total molar amount of the transition metal salt to lithium is 1:1.05. The mixture is mixed evenly in a ball mill, and then placed in a muffle furnace and calcined in oxygen at 700°C for 12 hours to obtain layered LiNi 0.9 Co0.05 Mn 0.05 O2.

[0089] Step 4. High temperature molten salt

[0090] The layered oxide material LiNi obtained in step 3 0.9 Co 0.05 Mn 0.05 O2 was mixed with KCl and NaCl in a mass ratio of 1:1:1, and then placed in a muffle furnace for calcination, heated to 680°C in an oxygen atmosphere, and calcined for 15 hours. The obtained powder material was fully washed with distilled water and dried to obtain a layered ordered@disordered core-shell composite high-nickel positive electrode material LiNi 0.9 Co 0.05 Mn 0.05 O2@Li 0.92 (Ni 0.9 Co 0.05 Mn 0.05 ) 1.08 O2.

[0091] The core-shell structure cathode material prepared in this embodiment has a layered structure The morphology is spherical, the particle size is about 8μm, and the thickness of the disordered shell is about 6nm.

[0092] Battery assembly and charge-discharge performance test: The battery assembly and battery charge-discharge test methods are the same as those in Example 1. The results show that the LiNi prepared in this example 0.9 Co 0.05 Mn 0.05 O2@Li 0.92 (Ni 0.9 Co 0.05 Mn 0.05 ) 1.08 The first discharge capacity of the O2 cathode material at 0.1C is 221 mAh g -1 ,like Figure 6 shown.

[0093] Example 5

[0094] In this embodiment, the ingredients are prepared according to the chemical formula LiNiO2.

[0095] A method for preparing LiNiO2@Li with different shell thicknesses 0.94 Ni 1.06 The method for O2 core-shell structure positive electrode material comprises the following steps:

[0096] Step 1. Solution preparation:

[0097] Weigh an appropriate amount of Ni(CH3COO)2·4H2O, add deionized water and stir to fully dissolve to prepare 3 mol L-1 Weigh sodium hydroxide solid and add deionized water to make a concentration of 8 mol L -1 precipitant solution; dilute the concentrated ammonia solution to 5 mol L -1 .

[0098] Step 2. Co-precipitation:

[0099] First, add 1L of deionized water to a 5L reactor, continuously introduce nitrogen into the reactor to expel oxygen in the reactor, and use a peristaltic pump to inject nickel salt solution and ammonia solution into the reactor from the feed port at feed rates of 0.8ml / min and 0.6ml / min respectively. At the same time, adjust the feed rate of sodium hydroxide solution to control the pH value of the solution in the reactor to 10.8. Control the reaction temperature to 50°C and the stirrer speed to 500r / min. After 75h of reaction, the product obtained in the reactor is filtered, washed, and dried to obtain a hydroxide precursor material.

[0100] Step 3. Calcination:

[0101] The hydroxide precursor particles obtained in step 2 are mixed with LiOH·H2O, and the ratio of the total molar amount of the transition metal salt to lithium is 1:1.06. The mixture is mixed evenly in a ball mill, and then placed in a muffle furnace and calcined at 600°C for 20 hours to obtain layered LiNiO2.

[0102] Step 4. High temperature molten salt

[0103] The layered oxide material LiNiO2 obtained in step 3 was mixed with LiCl in a mass ratio of 1:1, and then placed in a muffle furnace for calcination at 500°C in oxygen for 10 hours. The obtained powder material was fully washed with distilled water and dried to obtain a layered ordered@disordered core-shell composite high-nickel positive electrode material LiNiO2@Li 0.94 Ni 1.06 O2.

[0104] The core-shell structure cathode material prepared in this example is spherical in shape, with a particle size of about 12 μm and an XRD spectrum as shown in FIG. Figure 7 As shown in the figure, it can be seen that the prepared sample has a layered structure The thickness of the disordered shell is about 3 nm.

[0105] Battery assembly and charge-discharge performance test: The battery assembly and battery charge-discharge test methods are the same as those in Example 1. The results show that the LiNiO2@Li prepared in this example 0.94 Ni 1.06 The first discharge capacity of the O2 cathode material at 0.1C is 228 mAh g -1 ,like Figure 8 shown.

[0106] Based on the lithium-embedded oxide, this patent uses a high-temperature molten salt method and adjusts the roasting temperature and molten salt ratio to extract lithium / oxygen on the surface of the layered structure, which can effectively prepare Li(Ni) with different shell thicknesses. x Co y Mn 1-x-y )O2@Li 1-m (Ni x Co y Mn 1-x-y ) 1+m O2 core-shell structure material with excellent electrochemical properties.

[0107] The above contents are only for explaining the technical idea of ​​the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.

Claims

1. A method for preparing a layered ordered@disordered core-shell structure lithium ion battery positive electrode material, characterized in that: include: The hydroxide precursor or carbonate precursor is prepared by coprecipitation method, and then the layered ordered oxide Li(Ni) is prepared by high temperature calcination. x Co y Mn 1-x-y )O2, and then the layered ordered oxide Li(Ni x Co y Mn 1-x-y )O2 is uniformly mixed with an appropriate amount of molten salt and calcined at high temperature to extract the layered ordered structure Li(Ni x Co y Mn 1-x-y )O2 surface lithium / oxygen to obtain layered ordered@disordered core-shell structure lithium ion battery positive electrode material Li(Ni x Co y Mn 1-x-y )O2@Li 1-m (Ni x Co y Mn 1-x-y ) 1+m O2, where 0.05 ≤ m ≤ 0.15,0.60 ≤ x ≤ 1.00; 0.00 ≤ y ≤ 0.40; The specific steps include: 1) Prepare solution According to the chemical formula Li(Ni x Co y Mn 1-x-y )O2 ratio, 0.60 ≤ x ≤ 1.00; 0.00 ≤ y ≤ 0.40, weigh one or more nickel salts, cobalt salts and manganese salts, add water to fully dissolve and prepare a concentration of 0.5~3 mol·L -1 of saline solution; 2) Co-precipitation treatment Water, precipitant solution, ammonia buffer and the solution prepared in step 1) with a concentration of 0.5-3 mol·L -1 and a salt solution to obtain a mixed solution, wherein the pH value of the mixed solution is 8.0-12.0; stirring and reacting at 40-70°C for 1-100 hours, filtering, washing and drying the powder obtained by the reaction to obtain a precursor material; 3) High temperature calcination treatment The precursor material and lithium salt are mixed evenly, heated from room temperature to 600-800 °C in air or oxygen atmosphere, and calcined for 4-20 h to obtain the layered oxide material Li(Ni x Co y Mn 1-x-y )O2; 4) High temperature molten salt treatment The layered oxide material Li(Ni x Co y Mn 1-x-y )O2 and molten salt are mixed evenly, heated from room temperature to 500-900 °C in air or oxygen atmosphere, and calcined for 2-15 h. The calcined powder material is washed and dried to obtain a layered ordered@disordered core-shell structure lithium ion battery positive electrode material Li(Ni x Co y Mn 1-x-y )O2@Li 1-m (Ni x Co y Mn 1-x-y ) 1+m O2, 0.05 ≤ m ≤0.15; Layered oxide materials Li(Ni x Co y Mn 1-x-y )The mass ratio of O2 to molten salt is 1:1~1:5; the molten salt is one or more of Li2MoO4, NaCl, KCl, LiCl and LiNO3.

2. The method for preparing the layered ordered@disordered core-shell structure lithium ion battery positive electrode material according to claim 1, characterized in that: In step 1), the nickel salt is Ni(CH3COO)2·4H2O, NiSO4·6H2O, NiCl2·6H2O or Ni(NO3)2·6H2O; the cobalt salt is Co(CH3COO)2·4H2O, CoCl2·6H2O, CoSO4·7H2O or Co(NO3)2·6H2O; the manganese salt is Mn(CH3COO)2·4H2O, MnSO4·H2O, MnCl2·4H2O or Mn(NO3)2·4H2O.

3. The method for preparing the layered ordered@disordered core-shell structure lithium ion battery positive electrode material according to claim 1, characterized in that: In step 2), the concentration of the precipitant solution is 2~6 mol·L -1 , which is prepared by dissolving sodium hydroxide or sodium carbonate in water; the concentration of ammonia buffer is 1~10 mol·L -1 .

4. The method for preparing the layered ordered@disordered core-shell structure lithium ion battery positive electrode material according to claim 1, characterized in that: In step 2), the coprecipitation treatment is carried out in a reactor. 1L of deionized water is added to the reactor, and the concentrations of 0.5-3 mol·L -1 The salt solution, precipitant solution and ammonia buffer solution are added into the reactor; wherein the inlet rate of the salt solution is controlled to be 0.5-20 mL / min, and the inlet rate of the ammonia buffer solution is controlled to be 0.2-10 mL / min.

5. The method for preparing the layered ordered@disordered core-shell structure lithium ion battery positive electrode material according to claim 1, characterized in that: In step 2), the stirring reaction speed is controlled to be 200~500 r / min.

6. The method for preparing the layered ordered@disordered core-shell structure lithium ion battery positive electrode material according to claim 1, characterized in that: In step 3), the molar ratio of the precursor material to the lithium salt is 1:1.01~1:1.10; the lithium salt is LiOH·H2O, LiCH3COO, LiNO3 or Li2CO3.

7. A layered ordered@disordered core-shell structure lithium ion battery positive electrode material prepared by the preparation method according to any one of claims 1 to 6, characterized in that: The first discharge capacity ranges from 183 to 228 mAh g at 2.0 to 4.3 V and 0.1 C current density. -1 After 50 cycles, the capacity retention rate is over 90%.

8. Use of the layered ordered@disordered core-shell structure lithium ion battery positive electrode material according to claim 7 in the preparation of lithium ion batteries.

Citation Information

Patent Citations

  • Single-crystal high-nickel ternary positive electrode material and preparation method thereof

    CN109768231A

  • Production process for composite oxide, positive-electrode active material for lithium-ion secondary battery and lithium-ion secondary battery

    US20120315544A1